2021
DOI: 10.3389/fevo.2021.638568
|View full text |Cite
|
Sign up to set email alerts
|

CH4/CO2 Ratios and Carbon Isotope Enrichment Between Diet and Breath in Herbivorous Mammals

Abstract: Breath and diet samples were collected from 29 taxa of animals at the Zurich and Basel Zoos to characterize the carbon isotope enrichment between breath and diet. Diet samples were measured for δ13C and breath samples for CH4/CO2 ratios and for the respired component of δ13C using the Keeling plot approach. Different digestive physiologies included coprophagous and non-coprophagous hindgut fermenters, and non-ruminant and ruminant foregut fermenters. Isotope enrichments from diet to breath were 0.8 ± 0.9‰, 3.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Isotopic fractionation from diet to tooth takes place during enamel biomineralization. Large herbivore δ 13 C enamel values are enriched by ∼14.5 to 12.0 ± 1.0 compared to the plants that they consume, depending on their digestive strategies (Cerling and Harris, 1999;Tejada-Lara et al, 2018, Cerling et al, 2021. Generally, browsers have δ 13 C enamel values lower than -8 , grazers have values above -2 , and values in between are typical for mixed-feeders (Cerling and Harris, 1999;Uno et al, 2018).…”
Section: Carbon Isotopes In Tooth Enamelmentioning
confidence: 99%
“…Isotopic fractionation from diet to tooth takes place during enamel biomineralization. Large herbivore δ 13 C enamel values are enriched by ∼14.5 to 12.0 ± 1.0 compared to the plants that they consume, depending on their digestive strategies (Cerling and Harris, 1999;Tejada-Lara et al, 2018, Cerling et al, 2021. Generally, browsers have δ 13 C enamel values lower than -8 , grazers have values above -2 , and values in between are typical for mixed-feeders (Cerling and Harris, 1999;Uno et al, 2018).…”
Section: Carbon Isotopes In Tooth Enamelmentioning
confidence: 99%
“…Together, our meta-analysis and field study provide a strong framework for ecologists to select appropriate TDFs for interpreting isotopic values of consumer tissues. Although TDFs may be influenced by environmental conditions, physiological constraints, and digestive physiology (Barnes et al, 2007;Bloomfield et al, 2011;Cerling et al, 2021), which can vary among taxa, amino acid profiles of animal tissues are controlled by structural and metabolic requirements (Robbins, 1993;Robbins et al, 2005), and we suspect that the patterns, mechanisms, and isotopic offsets we observed are broadly applicable to other taxa. Our results suggest that variation in TDF-δ 13 C is driven primarily by dietary protein content and metabolic routing, which depend on both consumer class (i.e., herbivore, omnivore, or carnivore) and dietary sources (i.e., single or mixed).…”
Section: Discussionmentioning
confidence: 81%
“…We found strong evidence for dietary protein content influencing TDFs (both TDF‐δ 13 C and TDF‐δ 15 N), with patterns differing between single‐source and mixed diets for TDF‐δ 13 C. We suspect that these relationships would have been even stronger had we assessed dietary protein digestibility (e.g., Florin et al, 2011; Whiteman et al, 2021). Variability of TDF‐δ 13 C among herbivores may also have been influenced by differences in digestive physiology (Cerling et al, 2021). Patterns of decreasing TDF‐δ 15 N with increasing dietary protein are well documented in the literature (Adams & Sterner, 2000; Perga & Grey, 2010); however, the relationship between TDF‐δ 13 C and dietary protein content has been largely overlooked, likely because the pattern is obscured when data from single and mixed source diets are pooled.…”
Section: Discussionmentioning
confidence: 99%
“…The range for the elephantimorph taxa (i.e., gomphtheriids and mammutids) is -10.7‰ to -9.5‰, suggesting that they may have fed on more water-stressed browse than the relatively δ 13 C depleted deinotheriid. These differences could also be the result of body size variation (Tejada-Lara et al, 2018), plant parts consumed (Carlson and Kingston, 2014;Blumenthal et al, 2016), and interspecific physiological and metabolic variation (Cerling et al, 2021).…”
Section: Proboscideamentioning
confidence: 99%
“…The 18 O depleted δ 18 O enamel values in D. africanus compared to M. marymuunguae oxygen profiles is consistent with a dependence on a more 18 O depleted diet and water sources. Differences in body size and physiological metabolic processes could also have contributed to the divergent carbon and oxygen profiles between these two suoids (Bryant and Froelich, 1995;Kohn et al, 1996;Passey et al, 2005;Tejada-Lara et al, 2018;Cerling et al, 2021), as D. africanus is markedly smaller than M. marymuunguae (van der Made, 1996;Grossman, 2008). The higher δ 18 O enamel values for M. marymuunguae, however, do not follow the expectations outlined in Bryant and Froelich (1995) for a much larger species, where larger body sizes take in more liquid water and rely less on food metabolism for oxygen intake.…”
Section: Suoideamentioning
confidence: 99%